The New Museology Discourse at the Radyapustaka Surakarta Museum - Sugara, Badra; Warto, Warto; Pitana, Titis Srimuda (STKIP Singkawang, 2024)
This qualitative descriptive research, within the field of cultural studies, aims to explore the practice of New Museology discourse at the Radyapustaka Museum in Surakarta. The data sources included: informants, namely museum managers and visitors; the event location, the Radyapustaka Surakarta Museum; and relevant documents and references. Data collection was carried out through field observation, document studies, literature review, and interviews with selected informants using purposive and snowball sampling techniques. Data validity was ensured through triangulation, and data analysis was performed using interpretive techniques based on generalized propositions. The results of this study showed that activities carried out at the museum, such as exhibitions, workshops, and similar events, are practices of The New Museology discourse at the Radyapustaka Surakarta Museum.